IMPROVEMENT FOR AN ASSEMBLY FLOW FOR A GIVEN COMPONENT (1) - Ancuţa BĂLTEANU,; Monica BÂLDEA (Fiabilitate şi Durabilitate)
This study is carried out in a line of assembly of a finite wiring product. The assembly of this finished product is done in two specific sections. For the analysis of the activities in the assembly section, the timing method of the work stations was used. On the basis of the work times obtained and their centralization, the Keizen method was subsequently applied to obtain an improvement in the installation flow. Finally, a reduction in working times was achieved, as well as a more ergonomic arrangement of jobs. This paper is the first in a series of 3 papers to deal with this subject.